2021
DOI: 10.1096/fj.202100651r
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ASMT likely enhances the resistance of transgenic sheep to brucellosis by influencing immune‐related signaling pathways and gut microbiota

Abstract: Melatonin is a pleiotropic molecule with a variety of biological functions, which include its immunoregulatory action in mammals. Brucellosis is a worldwide endemic zoonotic disease caused by the Brucella, which not only causes huge economic losses for the livestock industry but also impacts human health. To target this problem, in current study, two marker‐free transgenic sheep overexpressing melatonin synthetic enzyme ASMT (acetylserotonin O‐methyltransferase) gene were generated and these melatonin enrich t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Importantly, melatonin prevented the death of premature newborn humans suffering from severe bacterial sepsis or septic shock [ 41 ] and melatonin has been suggested for use in individuals suffering from other serious bacterial infections, including necrotizing fasciitis [ 42 , 43 ]. Recently, elevated levels of endogenous melatonin were found to correlate with the ability to resist brucellosis infection [ 44 ]. As observed by Snider et al [ 45 ] in COVID-19-infected patients, excessive blood levels of sPLA2-IIA (a toxic phospholipase; see below) due to a bacterial infection are consequential in causing lung surfactant changes culminating in acute lung injury [ 46 ].…”
Section: Melatonin and Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, melatonin prevented the death of premature newborn humans suffering from severe bacterial sepsis or septic shock [ 41 ] and melatonin has been suggested for use in individuals suffering from other serious bacterial infections, including necrotizing fasciitis [ 42 , 43 ]. Recently, elevated levels of endogenous melatonin were found to correlate with the ability to resist brucellosis infection [ 44 ]. As observed by Snider et al [ 45 ] in COVID-19-infected patients, excessive blood levels of sPLA2-IIA (a toxic phospholipase; see below) due to a bacterial infection are consequential in causing lung surfactant changes culminating in acute lung injury [ 46 ].…”
Section: Melatonin and Sepsismentioning
confidence: 99%
“…Major contributors to the switch from mitochondrial glucose oxidation to the upregulation of pyruvate metabolism in the cytosol often are accompanied by stimulation of hypoxia-inducible factor-1α (HIF-1α) and activation of NF-ҝB and other transcription factors which exaggerate inflammation [53][54][55]. In COVID-19-infected patients, macrophages convert from M2 antiinflammatory to M1 pro-inflammatory cells which, along with other immune cells that exhibit a similar switch, contribute to the cytokine storm which leads to serious damage not only to the respiratory system but also in many other organs, thereby precipitating multiple organ failure [44,56] (Fig. 1).…”
Section: Melatonin/hif1α Interactionsmentioning
confidence: 99%
“… Ghareghani et al (2018) and Xiong et al (2022) demonstrated that melatonin modulates intestinal immune function through the expression of nod-like receptor-related genes and TLRs. By differential expression gene (DEG) and gene ontology (GO) analysis, Tlr1 , Tlr2 , Tlr7 , Cd14 , Naip , Cxcl8 and Nlrp1 , Nlrp3 gene expression levels were found to be significantly increased in ASMT (a key enzyme in the acetyl serine synthesis melatonin pathway) overexpressing transgenic sheep ( Li et al, 2021 ). It is suggested that melanin plays an important role by regulating anti-inflammatory related factors and signaling pathways.…”
Section: The Relationship Between Melatonin and Intestinal Microbiotamentioning
confidence: 99%
“…SNAT or ASMT overexpression in sheep improves their reserve/maximum capacity of synthetic melatonin function compared to WT. As a result, these transgenic sheep exhibit a high tolerance to LPS challenge and also display enhanced resistance to the infectious disease, brucellosis, compared to WT [ 104 , 105 ]. Considering the higher reserve capacity for melatonin synthesis in women compared to in men, women seem to possess a significant advantage over men in tolerating stressful conditions, such as those of infectious diseases [ 106 ].…”
Section: Discussionmentioning
confidence: 99%